Antibody treatment against pulmonary exposure to abrin confers significantly higher levels of protection than treatment against ricin intoxication. Issue 2 (2nd September 2015) - Sabo, Tamar; Gal, Yoav; Elhanany, Eitan; Sapoznikov, Anita; Falach, Reut; Mazor, Ohad; Kronman, Chanoch
Highlights Pulmonary exposure of mice to abrin leads to neutrophilic inflammation of the lungs. Lung pathology following abrin intoxication resembles that of ricin. Efficient Ab-based protection is achieved following abrin but not ricin exposure. Ab treatment against abrin, but not against ricin, reduces pulmonary IL-6 levels.